Exploring the Manuscript Tradition of Athonite Verse Prologues (On the Copy Hil. 436) - Čistiakova, Marina (Slavistica Vilnensis, 2025)
The library of the Hilandar Monastery has preserved nine copies of the Verse Prologue dating from the 14th to the 17th centuries, as well as two convolutes in which the Verse Prologue follows the monthly Service Menaion. Among these copies, particular attention is given to prologues that combine readings from both the Bulgarian and Serbian translations. This study focuses on manuscript Hil. 436, which contains the Verse Prologue for the period from March to August, and which was transcribed by the monk Savva in 1621. The aim of the research was to determine the composition and linguistic features of this manuscript. To establish its editorial affiliation, the content of the manuscript was systematically analyzed in comparison with the representatives of the Bulgarian and Serbian translations of the Verse Prologue. The analysis of copy Hil. 436 revealed that the section from March 10 to August 31 follows the Bulgarian translation, while the initial part, from March 1 to March 9, corresponds to the Serbian translation. Furthermore, the linguistic features of manuscript Hil. 436 indicate that no subsequent editorial revisions were introduced.